Bangla text classification using machine learning and deep learning techniques - Salehin, Kamrus; Ahmed, Fahim; Nabi, Md. Ashifun; Alam, M. Kaosar (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.